Social media marketing versus traditional marketing in the South African motor industry - Grobler, Elizna (University of the Free State, 2014)
Abstract not available
Dissertation (MBA (Business Management))--University of the Free State, 2014
Keywords: Motor industry -- South Africa -- Marketing; Internet marketing; Social media -- Marketing; Marketing